Gas‐Phase Oxidation of Methyl‐10‐undecenoate in a Jet‐Stirred Reactor. Issue 10 (2nd August 2017) - Meng, Xiangzan; Herbinet, Olivier; Coniglio, Lucie; Wang, Tianyou; Battin‐Leclerc, Frédérique
ABSTRACT: To better understand the chemistry of biodiesel surrogates, the gas‐phase oxidation of a C12 unsaturated methyl ester, methyl‐10‐undecenoate, has been studied in a jet‐stirred reactor in the temperature range 500–1100 K. These experiments were performed using neat fuel synthesized in the laboratory, with an initial fuel mole fraction set as 0.0021, at quasi‐atmospheric pressure (1.07 bar), at a residence time of 1.5 s with dilute mixtures in helium of equivalence ratios of 0.5, 1.0, and 2.0. The maximum obtained conversion was shown to be more than twice lower than that of methyl decanoate under the same conditions. This difference cannot be reproduced by the only published model for an unsaturated ester with a close number of carbon atoms (methyl‐9‐decenoate). A large range of products was quantified in addition to common oxidation products: saturated and unsaturated aldehydes, saturated and unsaturated methyl esters with a second carbonyl function, C2 –C10 alkenes, C4 –C10 dienes, C4 –C10 unsaturated methyl esters, C8 –C9 saturated methyl esters, and saturated, unsaturated, and hydroxyl methyl esters involving a cyclic ether. Pathways of formation for the products specific to unsaturated ester oxidation were proposed, and possible model improvements were discussed.